TINGKAT KENYAMANAN LINGKUNGAN BELAJAR FISIK DI MADRASAH IBTIDAIYAH INSAN CENDEKIA - Alinniah, Resta; Sopyana, Dita; Sputra, Karantiano (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The physical learning environment is one of the factors that directly influences students’ comfort and concentration during the learning process, yet it is often overlooked in the context of elementary education. This study aims to measure the level of comfort in the physical learning environment at Madrasah Ibtidaiyah Insan Cendekia, covering aspects of physical facilities, the school environment, and overall comfort. This study employs a quantitative approach using a survey method. Data were collected via a Likert-scale questionnaire distributed to 10 sixth-grade students as the study sample. The results indicate that the average overall comfort score is 79.60, which falls into the “High” category. However, when analyzed by indicator, the school environment indicator scored only 16.70 (Very Low category), physical facilities 25.20 (Low category), while the comfort indicator itself scored 37.60 (Very High category). These findings indicate that although students generally feel comfortable, there are structural aspects that still require serious attention and improvement.